Social spending, poverty, and immigration: A systematic analysis of welfare state effectiveness and nativity in 24 upper- and middle-income democracies - Amie Bostic; Allen Hyde (Luxembourg Income Study (LIS), 2023)
Previous research has highlighted the disadvantaged position immigrants often face in the economy, particularly when it comes to labor market outcomes such as employment or earnings. Extending this literature, the present study evaluates the economic exclusion of immigrants, conceptualized not as labor market outcomes but as relative poverty. This study examines the relationship between welfare generosity and immigrant poverty across rich western democracies and compares this relationship with that of native poverty. One publicly held belief is that immigrants disproportionately benefit from welfare generosity, while the literature on welfare chauvinism suggests greater social spending may not necessarily benefit immigrants. Furthermore, the effects may vary by spending and immigrant type. This study uses the Luxembourg Income Study to consider differences in the effects of welfare generosity on the odds an immigrant or native household is poor, how this effect varies by the type of spending, and how the effect changes depending on factors such as region of origin or citizenship status. Using four waves of data circa 2004 to 2014 across 24 upper- and middle-income democracies, the results show some support for welfare chauvinism and advantages to being an intra-EU immigrant and citizen immigrant.
Keywords: 330; poverty; immigration/migration; welfare states; inequality; welfare chauvinism